2014
DOI: 10.1016/j.otsr.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of recurrent dislocation after total hip arthroplasty

Abstract: Dislocation is a major complication of total hip arthroplasty (THA), whose frequency has been unaffected by improvements in surgical techniques and implants. The dislocation rate depends on multiple factors related to the patient, hip disease, and surgical procedure and is therefore also dependent on the surgeon. The many published studies on THA dislocation, its causes, and its treatment have produced conflicting results. The objective of this work is to review the management of THA dislocation, which is a se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 44 publications
0
47
0
2
Order By: Relevance
“…Thus, if component positioning is determined to be acceptable and the hip joint continues to be unstable, then trochanteric advancement may be a suitable choice [29]. For recurrent dislocation of hips, trochanteric advancement offers a surgical option for hip stability by re-tensioning the abductor muscles and increasing the lever arm [30]. In this study, the dislocation rate was lower than in other reports, and only one patient reported dislocation, which can be repaired by altering the position of the components or su cient repair of the short external rotators and securing greater trochanteric reattachment.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, if component positioning is determined to be acceptable and the hip joint continues to be unstable, then trochanteric advancement may be a suitable choice [29]. For recurrent dislocation of hips, trochanteric advancement offers a surgical option for hip stability by re-tensioning the abductor muscles and increasing the lever arm [30]. In this study, the dislocation rate was lower than in other reports, and only one patient reported dislocation, which can be repaired by altering the position of the components or su cient repair of the short external rotators and securing greater trochanteric reattachment.…”
Section: Discussionmentioning
confidence: 99%
“…There is no universally agreed stratagem 5 ; many authors propose identifying and addressing aetiological factors. 10,11 Multiple aetiologies often co-exist and successfully identifying and addressing these can be extremely challenging. Established treatment approaches including constrained liners have yielded relatively high rates of re-dislocation and failure.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not find any luxation or bone fracture near the implant, but this might be attributable to the character of the study group. Many authors have emphasized that the elevated risk of these complications occurs in female patients aged over 80 years and after previous surgical interventions in the hip joint ( Berry et al, 2004 ; Charissoux et al, 2014 ; Jolles et al, 2002 ; Lindahl et al, 2007 ; Meek et al, 2008 ), and such patients were not qualified for the study.…”
Section: Discussionmentioning
confidence: 99%